Quxie Capsule Alleviates Colitis-associated Colorectal Cancer Through Modulating the Gut Microbiota and Suppressing A. fumigatus-induced Aerobic Glycolysis. (November 2022) - Zhang, Zhiyong; Chen, Yuxi; Zheng, Yaojun; Wang, Lei; Shen, Sunan; Yang, Geliang; Yang, Yufei; Wang, Tingting
Aim: Quxie capsule (QX), a compound of 21 kinds of Traditional Chinese Medicine (TCM) herbs, has been used to treat patients with metastatic colorectal cancer (mCRC) and could suppress the growth of colon cancer. However, the mechanisms of QX inhibiting colorectal cancer remain unclear. In current study, we attempted to determine the anti-colorectal cancer (CRC) effects of QX and the mechanisms of QX in alleviating colorectal cancer. Methods: A colitis-associated colon cancer (CAC) model was established by intraperitoneally injecting mice with AOM followed by 3 cycles of 2% DSS in water. During establishment of CAC model, we orally gavaged mice with QX. Hematoxylin and eosin (H&E) and immunohistochemistry were performed to assess lesion of the colonic tumors. The expression of pro-inflammatory cytokines in colonic tumors was measured by qPCR. The proportion of immune cells in colonic tumors was analyzed by flow cytometry. Internal transcribed spacer (ITS) sequencing and 16S rRNA gene sequencing were performed to detect intestinal microbiota. The expression of glycolytic related enzymes, lactate production, and extracellular acidification rate (ECAR) were used to assess the level of aerobic glycolysis. Results: QX markedly inhibited intestinal tumorigenesis by decreasing the expression of pro-inflammatory cytokines and the proportion of myeloid-derived suppressor cells (MDSCs), and increasing the proportion of CD8 + T cells in colon tumors. Fecal microbiota sequencing revealed that QX increased the relative abundances of intestinal symbiotic probiotics, such as, Lactobacillus, Bifidobacterium and Faecalibacterium genera. What's more, opportunistic pathogens, Bacteroides genera and Aspergillus - Aspergillus fumigatus, exhibited remarkably reduced abundances in mice treated with QX compared with untreated CAC mice. Further experiments showed that QX significantly reduced glycolysis of colon tumor and suppressed A. fumigatus -induced glycolytic metabolism of colon cancer cells. Conclusions: QX alleviates the development of CRC at least in part through modulating intestinal microbiota and reducing A. fumigatus -induced aerobic glycolysis of colon cancer cells.